2007
DOI: 10.1163/156854107781352070
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence of entomopathogenic nematodes (Rhabditida: Steinernematidae) on golf courses in eastern Canada

Abstract: A survey of entomopathogenic nematodes from 38 golf courses was conducted in different climatic areas of Ontario and Québec provinces, Canada, during autumn 2002 and 2003. Soil samples were collected on golf course greens, fairways and roughs. Entomopathogenic nematodes were isolated from soil using wax moth (Galleria mellonella) and carrot weevil (Listronotus oregonensis) larvae as bait. Of the 436 samples (218 sites), 11 contained entomopathogenic nematodes for this study. All entomopathogenic nematode-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The presence of these families of nematodes was also noted in urban parks in the city of Barcelona, Spain (Hoyos & García del Pino, 2004), in turf grass in Ohio, USA (Alumai et al, 2006), and on golf courses in eastern Canada (Simard et al, 2007). Despite EPNs have been isolated from diverse ecosystems, natural habitats are more likely un contaminated by introduced nematodes and of fer a better chance of finding native species, in contrast to human modified areas (Stock et al, 1999;Stock & Gress, 2006).…”
mentioning
confidence: 79%
“…The presence of these families of nematodes was also noted in urban parks in the city of Barcelona, Spain (Hoyos & García del Pino, 2004), in turf grass in Ohio, USA (Alumai et al, 2006), and on golf courses in eastern Canada (Simard et al, 2007). Despite EPNs have been isolated from diverse ecosystems, natural habitats are more likely un contaminated by introduced nematodes and of fer a better chance of finding native species, in contrast to human modified areas (Stock et al, 1999;Stock & Gress, 2006).…”
mentioning
confidence: 79%
“…Therefore, early detection of PPNs in infected areas and correct diagnosis of these organisms are important for healthy and sustainable management of turfgrass areas (McClure et al, 2012). Studies have been carried out on the detection of damaging nematode species and their economic losses in turfgrass fields in different countries (Azevedo de Oliveira et al, 2018; Bélair et al, 2006; Jordan & Mitkowski, 2006; Khan et al, 2008; Little, 2019; McClure et al, 2012; Mwamula & Lee, 2021; Oka et al, 2004; Simard et al, 2008; Vandenbossche et al, 2011; Viaene et al, 2007; Walker et al, 2002; Yu et al, 1998; Zeng et al, 2012). In the study conducted in the United States, 24 PPN species belonging to 19 genera were identified (Zeng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several members of beetles from the family Scarabaeidae, Phyllophaga spp. Harris, Rhizotrogus majalis (Razoumowsky), Popillia japonica Newman and Melolontha melolontha (L.), are important pests of grass sward and ornamental plants in Europe and North America (Simard et al, 2001). Adult beetles feed with leaves and flowers of fruit and forest trees and of ornamental plants, meanwhile larvae -white grubs -are soil pests and they feed on belowground parts of the plants (Keller and Zimmermann, 2005).…”
Section: Introductionmentioning
confidence: 99%